Protection Standardization Towards Unemployment in Indonesia - Saputra, Beny; Bene, Olivér (Jambe Law Journal, 2022)
The Covid-19 pandemic triggered a significant recession ranging from 4.4 percent to 5.2 percent. As seen by the high rate of layoffs, the labor market is one of the most impacted industries. To counteract this scenario, the government has implemented a job loss insurance system as part of its broader protection against unemployment program. This research discusses the standarization of Jaminan Kehilangan Pekerjaan (Job Insurance Scheme) in Indonesia with five key principal of the ILO Convention no 168 and its objectives. The method used in this research is comparative law. In analysing legal materials, this research uses qualitative descriptive analysis with using key factor and objective of ILO convention. this study found that JKP or Job loss insurance scheme in Indonesia meet five key principal of the ILO Convention and the objectives